SOME OF SEMEN PHYSICAL PROPERTIES (VOLUME AND MOTILITY) OF GERMAN SHEPHERD DOGS REARED IN IRAQ DURING DIFFERENT MONTHS OF THE YEAR. - Karem, Rafid H.; Karem, Rafid H.; Ibrahim, Najlaa S.; Zaid, Nazih W. (International Journal of Psychosocial Rehabilitation, 2020)
A total of five German shepherd dogs were selected for Breeding Soundness Examination (BSE). From the resources of the Iraqi Ministry of Interior, all of them live in uniform living conditions, and are subject to constant veterinary supervision. The collection was weekly from each dog, and 120 ejaculations were collected during all months. In this study, we studied the physical properties (volume, mass motility and individual motility) of the seminal fluid of the German Shepherd dogs (GSD) breed during the six-month period (October, November and December 2019) and (January, February and March 2020). The method of semen collection was by digital manipulation. It was recorded that volume, mass motility and individual motility show significant differences at level of (P<0.05) in six-month of the study. total semen volume (ml), total Mass motility (Scale 1-5) and total Individual motility (%), were 32.8±1.444482 ml, 3.308333±0.001792 and 87.75±0.216562, respectively. In the present study all the German shepherd dogs were affected by climatic conditions and temperature changes inside Iraq. But it is suitable for future reproduction.